The complexity of modern asymmetric warfare - Manwaring, Max G. (International security affairs, 2012)
Today more than one hundred small, asymmetric, and revolutionary wars are being waged around the world. This book provides invaluable tools for fighting such wars by taking enemy perspectives into consideration. The challenge presented to civilian and military leaders is to take probable enemy perspectives into consideration, and turn resultant conceptions into strategic victories.